Herpes zoster in the radial nerve distribution in an 8 years old healthy child-a case report - Edris, Hala; Abualiat, Abdullah; Mordy, Ayed Al (International Journal of Research in Medical Sciences, 2017)
Varicella zoster is an omnipresent virus which commonly affects childhood as chicken pox. Although the primary infection is self-limiting and seldom severe, the virus remains dormant in the body. The virus resides in the dorsal root or cranial nerve ganglion and reactivation may occur years later as herpes zoster or "Shingles". Herpes zoster (HZ) can occur at any age but is rare in childhood and adolescents. Old aged and immunosuppressed subjects are at risk for developing the disease. The most common area involved in HZ is the trunk (dermatomes innervated by the thoracic nerves) and rarely presents exclusively in the upper extremity. We report a case of HZ isolated to the radial nerve distribution in a healthy 8 years boy. The reported case reveals the importance of considering zoster infection in young age, or uncommon sites when evaluating the onset of pain in a dermatomal distribution specially if associated with vesiculobullous rash.